The text of the Hebrew Bible and its editions: studies in celebration of the fifth centennial of the complutensian polyglot - Piquer Otero, Andrés; Torijano, Pablo A.; Lange, Armin; Trebolle Barrera, Julio C. (Supplements to the textual history of the Bible, 2017)
Front Matter /Andrés Piquer Otero and Pablo Torijano Morales -- The First Polyglot Bible /Natalio Fernández Marcos -- From Polyglot to Hypertext /Ronald Hendel -- Methodological Considerations in the Preparation of an Edition of the Hebrew Bible /Michael Segal -- The Conundrum of Scriptural Plurality: The Arabic Bible, Polyglots, and Medieval Predecessors of Biblical Criticism /Ronny Vollandt -- Electronic Scripture Editions (With an Appendix Listing Electronic Editions on the Internet [2014]) /Emanuel Tov -- A Critical Edition of the Hebrew Bible between the Dead Sea Scrolls to the Masoretic Text /Armin Lange -- How Old is the Targumic Tradition? Traces of the Jewish Targum in the Second Temple Period, and Vice Versa /Jan Joosten -- Textual History of the Septuagint and the Principles of Critical Editing /Anneli Aejmelaeus -- From Secondary Versions through Greek Recensions to Hebrew Editions. The Contribution of the Old Latin version /Julio Trebolle Barrera -- Glimpses into the History of the Hebrew Bible Through the Vulgate Tradition, With Special Reference to Vulgate MS θG /Michael Graves -- Prolegomena to a (Critical) Edition of Syrohexapla /Ignacio Carbajosa Pérez -- A “New Field” for the Twenty-First Century? Rationale for the Hexapla Project, and a Report on Its Progress /Alison Salvesen -- Deuteronomy as a Test Case for an Eclectic Critical Edition of the Hebrew Bible /Sidnie White Crawford -- The Textual Plurality of the Book of Joshua and the Need for a Digital Complutensian Polyglot Bible /Kristin De Troyer -- ‮מלכים‬‎, Βασιλειῶν, Reges: Textual Plurality as a Constellation Cluster and the Challenge of Editing a Star-Map /Andrés Piquer Otero and Pablo Torijano Morales -- Jeremiah Amid Actual and Virtual Editions: Textual Plurality and the Editing of the Book of Jeremiah /Richard D. Weis -- The Hebrew Bible Critical Edition of Isaiah 40:1–12 /Eugene Ulrich -- Textual Issues for an Edition of the Minor Prophets /Russel E. Fuller -- Compositions and Editions in Early Judaism. The Case of Daniel /Arie van der Kooij -- Problems and Poetics in the Text History of Job /Brent A. Strawn -- Quotations of Jewish Scriptures in Hebrew Texts /Armin Lange and Russell Fuller -- Quotations of Jewish Scriptures in Greek and Latin Texts /Martin Meiser -- Indexes /Andrés Piquer Otero and Pablo Torijano Morales.